2020
DOI: 10.3389/fnbeh.2020.583395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aggressive Experience in Female Syrian Hamsters on Glutamate Receptor Expression in the Nucleus Accumbens

Abstract: Our social relationships determine our health and well-being. In rodent models, there is now strong support for the rewarding properties of aggressive or assertive behaviors to be critical for the expression and development of adaptive social relationships, buffering from stress and protecting from the development of psychiatric disorders such as depression. However, due to the false belief that aggression is not a part of the normal repertoire of social behaviors displayed by females, almost nothing is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 123 publications
1
13
0
Order By: Relevance
“…Aggression among male laboratory mice is a complex issue. Aggression is a natural component of rodent behaviour and has rewarding properties [ 139 ], so providing mice with the freedom to express some of this behaviour (so long as subordinates can escape without harm) could be considered to provide welfare benefits. It is possible that previous studies have failed to provide sufficient quantities of enrichment to mitigate competition [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aggression among male laboratory mice is a complex issue. Aggression is a natural component of rodent behaviour and has rewarding properties [ 139 ], so providing mice with the freedom to express some of this behaviour (so long as subordinates can escape without harm) could be considered to provide welfare benefits. It is possible that previous studies have failed to provide sufficient quantities of enrichment to mitigate competition [ 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our gene enrichment analysis indicated dramatically down-regulation of RNA editing in specific gene functions and pathways in winners, especially biological processes related to the G protein–coupled glutamate receptor signaling pathway and high voltage–gated calcium channel activity. Aggressive experience in female Syrian hamsters resulted in an increased expression of postsynaptic density, AMPA receptors, and Group I metabotropic glutamate receptors ( 54 ). Increased aggression was reported in knock-out mice of genes encoding voltage-gated calcium channels ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also an appetitive component of aggression (for the aggressor); Golden et al demonstrated that aggressive mice developed a conditioned place preference for a location where they were able to attack an intruder mouse 45 . In another study using female Syrian hamsters, aggressive encounters resulted in behavioural and neurological changes associated with rewarding effects 46 . In the current study, the playpen allowed for expression of more agonistic behaviours, notably chasing initiated by C57 mice, which cannot occur to the same extent in shoebox cages.…”
Section: Discussionmentioning
confidence: 99%